Impossible - Amado, Elisa 1946- (Groundwood Books, 2021)
"A funny story about a seemingly impossible child and his desperate parents, who enlist the help of a specialist with unexpected results ... Toribio is two years old and his parents love him very much, but some days, taking care of him feels like an impossible task. He won't sleep, makes a fuss when eating, splashes his bath water everywhere, and refuses to use his potty. At the end of the day, Toribio's parents are exhausted. So when they see an ad for a specialist who can solve any type of problem, his desperate parents make an appointment right away. Mrs. Meridien's methods deliver overnight results, but her solution isn't quite what they had in mind ... Impossible is a funny story with a surprise ending that will delight young children and exhausted parents alike."--
Keywords: Kind; Gehorsam; Katze; Eltern; Wunsch; Erziehung; Metamorphose; Parent and child / Juvenile fiction; Parenting / Juvenile fiction; Toddlers / Juvenile fiction; Parent and child / Fiction; Parenting / Fiction; Toddlers / Fiction; JUVENILE FICTION / Family / General; JUVENILE FICTION / Humorous Stories; Parent and child; Parenting; Toddlers; Picture books; Fiction; Juvenile works; Children's stories / Pictorial works; Bilderbuch